PHOTOGRAPHER INCOM EARNINGS PRE-WEDDING IN PERSPECTIVE AL-'AMÂL. IJÂRAH CONTRACT. Research in Takengon City - Dissarami M. Samin (Universitas Islam Negeri Ar-Raniry, 2022)
Pre-wedding photo shoots are carried out to meet various aesthetic needs at the wedding ceremony. This causes many people to need the services of a photographer, producing various forms of style from every pre-wedding photo moment that is created. There are three problem formulations in this thesis, namely first, how is the contribution of the photographer in determining behavior and style in pre-wedding shooting. Second, what are the efforts made by the photographer to avoid photo sessions that are against the syara' in pre-wedding photography. Third, what are the consequences of the photographer's income according to the perspective of the ijarah al-'amal contract in Takengon City. The method that the author uses in this research is a qualitative descriptive method, the data collection used is through library researchers and field researchers, carried out by researching and asking questions to the photographer in Takengon City. The results of the study show that first, the participation of photographers in the photo-taking process to avoid things that are contrary to sharia. Second, in the photo session there were several photographers giving rules and restrictions to clients to avoid things that are contrary to sharia rules. Third, the photographer's income has met the terms and conditions based on the ijarah al-amal agreement